Odonata of Maharashtra, India with Notes on Species Distribution. Issue 1 (15th April 2015) - Tiple, Ashish D.; Koparde, Pankaj
Abstract : Odonata are freshwater insects spread world-wide. Tropical areas are high Odonata diversity areas. However, there has not been accumulation of extensive baseline data on spatial distribution of these insects from such places. Maharashtra, the third largest state of India, harbors a variety of land-use and occupies six biogeographic provinces. We carried out Odonata surveys in Maharashtra during 2006–2014. Compilation of all these studies along with other authenticated records resulted in a checklist of 134 species of Odonata belonging to 70 genera representing 11 families. The highest numbers of species were recorded from the Libellulidae (48 species) and Gomphidae (22 species) families. A previous study had reported 99 species of Odonata from the Maharashtra state considering records from early 1900's to 2012. Our observations across the state add 33 species to this list. Maharashtra forms a unique source of Odonata diversity and our observations support the importance of this region in providing valuable habitats for Odonata. Here, we discuss several of the new records, how global surveys might help fill the local gap in species distributions, how secondary data deposited through crowd-sourcing can help and what it offers to conservation.